Politics of affect in Train to Pakistan and Tamas - Joshi, Dipak Raj (Contemporary Research: An Interdisciplinary Academic Journal, 2020)
This paper analyzes selected Indian partition novels to unravel affective politics underlined in them. The major affects underlying in these novels are those of love, hatred, happiness, unhappiness, and outrage. One positive affect in favor of one concomitantly invites antonymic affect for the other. This refrain of affect, as this paper has tried to analyze, follows the nationalist historiographies of the writers like Khushwant Singh (The Train to Pakistan) and Bhisham Sahni (Tamas). The paper concludes that the affects evoked by the above mentioned novels are ethically tilted to the notions of community and nationhood of the respective writers—an ideologically biased orientation that results into a prose of demonization and denunciation of whom they consider the Other.